Understanding Tuberculosis Analyzing the Origin of Mycobacterium Tuberculosis Pathogenicity - Cardona, Pere-Joan (IntechOpen, 2012)
Mycobacterium tuberculosis in an attempt to understand the extent to which the bacilli has adapted itself to the host and to its final target. On the other hand, there is a section in which other specialists discuss how to manipulate this immune response to obtain innovative prophylactic and therapeutic approaches to truncate the intimal co-evolution between Mycobacterium tuberculosis and the Homo sapiens.